Electrolytic removal of zinc from simulated chloride wastewaters using a novel flow-by fixed bed electrochemical reactor - Mohammed, Sawsan A. M.; Sulaymon, Abbas Hamid; Abbar, Ali Hussein (Iraqi Journal of Chemical and Petroleum Engineering, 2015)
The cathodic deposition of zinc from simulated chloride wastewater was used to characterize the mass transport properties of a flow-by fixed bed electrochemical reactor composed of vertical stack  of stainless steel nets, operated in batch-recycle mode. The electrochemical reactor employed potential value in such a way that the zinc reduction occurred under mass transport control. This potential was determined by hydrodynamic voltammetry using a borate/chloride solution as supporting electrolyte on stainless steel rotating disc electrode. The results indicate that mass transfer coefficient (Km) increases with increasing of flow rate (Q) where .The electrochemical reactor proved to be efficient in removing zinc and was able to reduce the levels of this metal to lower than 0.7 ppm starting from initial concentration of 48.4 mg dm-3 ppm in 120 minutes using ratio of cathode volume/catholyte volume equal to 0.0075. Sherwood and Reynolds numbers were correlated to characterize the mass transport properties of the reactor as follows: